2023
DOI: 10.3390/plants12152813
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Profiling and Antiviral Activity of Green Sustainable Nanoparticles Derived from Maesa indica (Roxb.) Sweet against Human Coronavirus 229E

Fatma Alzahra M. Abdelgawad,
Seham S. El-Hawary,
Essam M. Abd El-Kader
et al.

Abstract: Plant secondary metabolites are key components for new, safe and effective drugs. Ethanolic extract of Maesa indica Roxb. Sweet (ME) aerial parts were used for biosynthesis of sustainable green zinc oxide nanoparticles (ZnO NPs) with an average particle size 6.80 ± 1.47 nm and zeta potential −19.7 mV. Both transmission electron microscopy and X-ray diffraction assay confirmed the hexagonal shape of ZnO NPs. Phenolic ingredients in ME were identified using LC-ESI-MS/MS-MRM revealing the identification of chloro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Additionally, the zeta potential value gives important information regarding the surface charge characteristics of ZnONPs, implying their potential for stable dispersion in neutral aqueous environments. Our data was very similar to those reported by Abdelbaky et al (2022) and Abdelgawad et al (2023) and more stable than ZnO nanoparticles prepared by Iqbal et al (2021) . The FTIR analysis was also utilized to study the functional groups in charge of ZnONPs production and stability including CH, C=O, C=C, C-O, C-N, and C-C-.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, the zeta potential value gives important information regarding the surface charge characteristics of ZnONPs, implying their potential for stable dispersion in neutral aqueous environments. Our data was very similar to those reported by Abdelbaky et al (2022) and Abdelgawad et al (2023) and more stable than ZnO nanoparticles prepared by Iqbal et al (2021) . The FTIR analysis was also utilized to study the functional groups in charge of ZnONPs production and stability including CH, C=O, C=C, C-O, C-N, and C-C-.…”
Section: Discussionsupporting
confidence: 92%
“…All of these results confirmed the lung-protecting effect of the ethanolic extract of Maesa indica. This plant is rich in secondary metabolites, especially those which have antioxidant effects, such as phenolic and flavonoid compounds [5]. In this study, we identified 26 flavonoid compounds and 8 phenolic compounds.…”
Section: Histopathological Findingsmentioning
confidence: 99%
“…Kaempferol has proved to be a strong antioxidant, and it could significantly reduce the damage caused by lung ischemia-reperfusion injuries by inhibiting the release of inflammatory factors including interleukin lung ischemia-reperfusion injury and tumor necrosis factor α into All of these results confirmed the lung-protecting effect of the ethanolic extract of Maesa indica. This plant is rich in secondary metabolites, especially those which have antioxidant effects, such as phenolic and flavonoid compounds [5]. In this study, we identified 26 flavonoid compounds and 8 phenolic compounds.…”
Section: Histopathological Findingsmentioning
confidence: 99%
See 1 more Smart Citation